Coexisting autoantibodies against transcription factor Sp4 are associated with decreased cancer risk in patients with dermatomyositis with anti-TIF1γ autoantibodies. Issue 2 (25th August 2022) - Hosono, Yuji; Sie, Brandon; Pinal-Fernandez, Iago; Pak, Katherine; Mecoli, Christopher A; Casal-Dominguez, Maria; Warner, Blake M; Kaplan, Mariana J; Albayda, Jemima; Danoff, Sonye; Lloyd, Thomas E; Paik, Julie J; et al.
Abstract : Objectives: In dermatomyositis (DM), autoantibodies are associated with unique clinical phenotypes. For example, anti-TIF1γ autoantibodies are associated with an increased risk of cancer. The purpose of this study was to discover novel DM autoantibodies. Methods: Phage ImmunoPrecipitation Sequencing using sera from 43 patients with DM suggested that transcription factor Sp4 is a novel autoantigen; this was confirmed by showing that patient sera immunoprecipitated full-length Sp4 protein. Sera from 371 Johns Hopkins patients with myositis (255 with DM, 28 with antisynthetase syndrome, 40 with immune-mediated necrotising myopathy, 29 with inclusion body myositis and 19 with polymyositis), 80 rheumatological disease controls (25 with Sjogren's syndrome, 25 with systemic lupus erythematosus and 30 with rheumatoid arthritis (RA)) and 200 healthy comparators were screened for anti-SP4 autoantibodies by ELISA. A validation cohort of 46 anti-TIF1γ-positive patient sera from the University of Pittsburgh was also screened for anti-Sp4 autoantibodies. Results: Anti-Sp4 autoantibodies were present in 27 (10.5%) patients with DM and 1 (3.3%) patient with RA but not in other clinical groups. In patients with DM, 96.3% of anti-Sp4 autoantibodies were detected in those with anti-TIF1γ autoantibodies. Among 26 TIF1γ-positive patients with anti-Sp4 autoantibodies, none (0%) had cancer. In contrast, among 35 TIF1γ-positive patients without anti-Sp4 autoantibodies, 5 (14%, p=0.04) had cancer. In the validation cohort, among 15 TIF1γ-positive patients with anti-Sp4 autoantibodies, 2 (13.3%) had cancer. By comparison, among 31 TIF1γ-positive patients without anti-Sp4 autoantibodies, 21 (67.7%, p<0.001) had cancer. Conclusions: Anti-Sp4 autoantibodies appear to identify a subgroup of anti-TIF1γ-positive DM patients with lower cancer risk.